Paramagnetic properties of chernozem typical humic acids and their change under different soil tillage - Popirny, M.A. (AgroChemistry and Soil Science, 2016)
As a result of physical-chemical analysis there were revealed the structural features of the transformation of humic acids of chernozem typical under the influence of minimized, no till and traditional methods of soil tillage. It was investigated the mechanism of structural transformation of humic acids under different soil tillage, by electron paramagnetic resonance (EPR). It was found that for the ordinary tillage of chernozem typical there was an increase in spin signal allocated preparations of humic acids, due process chelates and macrocyclic effect.